The effectiveness of an emotional freedom technique (EFT) on anxiety and post-traumatic stress disorder (PTSD) in women with spontaneous abortion - Yavari Kermani, Maryam; Razavi , Sepideh; Shabani , Mohammad ghassem (Applied Family Therapy Journal (AFTJ), 2020)
Aim: The present study aimed to determine the effectiveness of an emotional freedom technique on anxiety and post-traumatic stress disorder (PTSD) in women with spontaneous abortion. Method: The present study was a single-case experimental design with an asynchronous multiple baseline type. We selected 6 out of 21 women with abortion trauma at Shahid Beheshti Hospital in Isfahan in April and May 2019 using the purposive sampling and after screening by Spielberger anxiety inventory (1983), and the Self-report post-traumatic stress disorder symptom scale by Foa, Riggs, Dancu, & Rothbaum (1993). The women were individually treated in sessions of emotional freedom techniques by Church (2014) in twelve forty-five minute sessions with two follow-up stages. We analyzed the data by visual mapping, stable change index, and recovery percentage formula. Results: The results indicated that the emotional freedom technique intervention among participating women reduced trait anxiety in the treatment phase (38.75% recovery) and follow-up phase (43.06%), state anxiety in the treatment phase (47.14% recovery) and follow-up phase (47.91%), and post-traumatic stress disorder in the treatment phase (49.92% recovery) and follow-up phase (50.29%). Conclusion: The results indicated that the use of the treatment for individuals suffering from PTSD and other associated disorders, including anxiety, could help to simultaneously improve both problems.